Traditional Languages Utilization on Tourism Villages as an Effort of Cultural Advancement - Imam Nur Hakim; Siti Hamidah (Nusantara Science and Technology Proceedings, 2023)
Efforts to utilize traditional languages as cultural objects continue to be accelerated after the emergence of Law Number 5 of 2017 concerning the Advancement of Culture (UUPK). As a priority cultural object, the scarcity of traditional languages due to acculturation and lack of interest in making it a daily language is needed to make tactical efforts to implement UUPK in every critical sector, including tourism. Through tourism village products, efforts to utilize traditional languages become integral to enriching the village's attractiveness. Thus, through proper utilization steps, tourism villagers can achieve the goal of cultural advancement through tourism activities. Unfortunately, this critical effort has not been clearly described. Scholars have observed no model of traditional language utilization in independent tourism village groups. This research raises the urgency to identify models of traditional Javanese language utilization and present new solutions to the problem of traditional language scarcity through tourism villages. As a result, independent tourism villages that make the Javanese language an attraction have a spectrum in the use of traditional languages in terms of principles, objectives, and technical efforts to utilize traditional language cultural objects.